ANSWER I WILL MARK U AS BRANLIEST..
Attachments:
![](https://hi-static.z-dn.net/files/d55/a4257a4bb112e595d513d06b9be87e47.jpg)
Answers
Answered by
1
Step-by-step explanation:
We have, 6/ 2x – (3 – 4x) = 2/3 6/(2x – 3 + 4x) = 2/3 6/(6x – 3) = 2/3
Let us perform cross-multiplication we get, 3(6) = 2(6x – 3) 18 = 12x – 6 12x = 18 + 6 12x = 24 x = 24/12 = 2
Now let us verify the given equation, 6/ 2x – (3 – 4x) = 2/3 6/(6x – 3) = 2/
By substituting the value of ‘x’ we get, 6/ (6(2) – 3) = 2/3 6/(12-3) = 2/3 6/9 = 2/3 2/3 = 2/3
Hence, the given equation is verified.
Answered by
1
Step-by-step explanation:
pls mark as brainlist
I hope it's help u
Attachments:
![](https://hi-static.z-dn.net/files/d3e/9e533b62129b5e253f20da46be0eab16.jpg)
Similar questions